3(4x-5)+2=4x-11

Simplify each term.

Apply the distributive property.

3(4x)+3⋅-5+2=4x-11

Multiply 4 by 3.

12x+3⋅-5+2=4x-11

Multiply 3 by -5.

12x-15+2=4x-11

12x-15+2=4x-11

Add -15 and 2.

12x-13=4x-11

12x-13=4x-11

Subtract 4x from both sides of the equation.

12x-13-4x=-11

Subtract 4x from 12x.

8x-13=-11

8x-13=-11

Add 13 to both sides of the equation.

8x=-11+13

Add -11 and 13.

8x=2

8x=2

Divide each term in 8x=2 by 8.

8×8=28

Cancel the common factor of 8.

Cancel the common factor.

8×8=28

Divide x by 1.

x=28

x=28

Cancel the common factor of 2 and 8.

Factor 2 out of 2.

x=2(1)8

Cancel the common factors.

Factor 2 out of 8.

x=2⋅12⋅4

Cancel the common factor.

x=2⋅12⋅4

Rewrite the expression.

x=14

x=14

x=14

x=14

The result can be shown in multiple forms.

Exact Form:

x=14

Decimal Form:

x=0.25

Solve for x 3(4x-5)+2=4x-11